ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGEMBALIAN PINJAMAN UMKM MITRA BINAAN PT ANTAM DI JABODETABEK - Roy Prakoso; Mulyadi Mulyadi (Universitas Pakuan, 2019)
The purpose of this study is to examine several factors that influence the level of CSR funds fostered by partners of PT Antam (Persero) Tbk in Jabodetabek. The sample of this study were 52 SMEs fostered by PT Antam (Persero) Tbk. Sampling is done by Probability sampling, with proportional random sampling technique. The data analysis method used is multiple linear regression. From the results of the study it was found that the size of the loan, sales turnover, business duration and business assets did not affect the rate of repayment of the loan while religiosity affect the rate of repayment of the loan. Thus, in order to achieve the level of repayment of MSME fostered partners of PT Antam (Persero) Tbk, PT Antam (Persero) Tbk must pay attention to the level of religiosity in providing loans to prospective fostered partners.